2013
DOI: 10.5897/ajpp12.505
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescribing pattern in a referral hospital in Ethiopia

Abstract: Antibiotics are drugs used for treating infectious disease such as bacterial infections, fungal infections and some parasitic infection but unwise use may contribute to resistance development and poor management of infectious diseases. Though pattern of antibiotic use was determined in different parts of Ethiopia, it is not known in Dessie referral hospital (DRH). This study aimed to assess antibiotic prescribing pattern in Dessie Referral hospital, Northeast Ethiopia, in January, 2012. Retrospective study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 9 publications
3
23
5
Order By: Relevance
“…Most of the stored antimicrobials were penicillin and derivatives, metronidazole, and antimalarials. Penicillin consumption is frequently mentioned in other similar studies, including studies from Ethiopia (Gebeyehu et al, 2015;Desalegn, 2013;Fenta et al, 2013;Getachew et al, 2013), Uganda (Ocan et al, 2014), Indonesia (Widayati et al, 2011), and Guatemala (Ramay et al, 2015).…”
Section: Discussionmentioning
confidence: 84%
“…Most of the stored antimicrobials were penicillin and derivatives, metronidazole, and antimalarials. Penicillin consumption is frequently mentioned in other similar studies, including studies from Ethiopia (Gebeyehu et al, 2015;Desalegn, 2013;Fenta et al, 2013;Getachew et al, 2013), Uganda (Ocan et al, 2014), Indonesia (Widayati et al, 2011), and Guatemala (Ramay et al, 2015).…”
Section: Discussionmentioning
confidence: 84%
“…This result is comparable to the study done in Uganda [ 46 ], Indonesia [ 47 ], Guatemala [ 48 ], Greek [ 14 , 41 ], and Mongolia [ 29 ], which reported that Amoxicillin was the most common antibiotics used by the study participants. Health facility studies in Ethiopia showed that Amoxicillin was most commonly prescribed antibiotic from which its common use in community could arise [ 49 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was dissimilar to previous studies where majority of antimicrobials were given by oral route. 20,21 Most of the prescriptions were collected from the wards; this may be the reason for prescribing more injectable formulations.…”
Section: Discussionmentioning
confidence: 99%